The escape - Baldacci, David (New York : Grand Central Publishing, 2014)
When John Puller's older brother Robert inexplicably escapes from the military's most secure prison, Puller finds himself part of an investigation to hunt down his own brother. As he digs more deeply into the case, Puller discovers that someone is out there who doesn't want the truth to ever come out.
Keywords: United States. -- Army Criminal Investigation Command -- Fiction; Brothers -- Fiction; Escaped prisoners -- Fiction; Suspense fiction